2019
DOI: 10.3390/rs11091054
|View full text |Cite
|
Sign up to set email alerts
|

Retrieving Phytoplankton Size Class from the Absorption Coefficient and Chlorophyll A Concentration Based on Support Vector Machine

Abstract: The phytoplankton size class (PSC) plays an important role in biogeochemical processes in the ocean. In this study, a regional model of PSCs is proposed to retrieve vertical PSCs from the total minus water absorption coefficient (at-w(λ)) and Chlorophyll a concentration (Chla). The PSC model is developed by first reconstructing phytoplankton absorption and Chla from at-w(λ), and then extracting PSC from them using the support vector machine (SVM). In situ bio-optical data collected in the South China Sea from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 62 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…However, more suitable algorithms were found and kernel-based extreme learning machine (KELM) generally performed the best (49 and 57 out of 100 repetitions for reflectance and first derivative spectra, respectively) for estimating the chlorophyll content when assessed using the ratio of performance to deviation (RPD) values. Although SVM's robustness has been reported in some studies [59][60][61], and it performed best in 20 and 37 of the repeats, it also showed the worst performance in 28 and 33 repetitions for the reflectance and first derivative spectra, respectively. These results strongly suggest that SVM is not a stable method.…”
Section: Performance Of Different Machine Learning Algorithmsmentioning
confidence: 87%
“…However, more suitable algorithms were found and kernel-based extreme learning machine (KELM) generally performed the best (49 and 57 out of 100 repetitions for reflectance and first derivative spectra, respectively) for estimating the chlorophyll content when assessed using the ratio of performance to deviation (RPD) values. Although SVM's robustness has been reported in some studies [59][60][61], and it performed best in 20 and 37 of the repeats, it also showed the worst performance in 28 and 33 repetitions for the reflectance and first derivative spectra, respectively. These results strongly suggest that SVM is not a stable method.…”
Section: Performance Of Different Machine Learning Algorithmsmentioning
confidence: 87%
“…SVM theory is an approximation of the principle of structural risk minimization that involves the same processing complexity for high-and low-dimensional samples. Kernel functions are introduced to realize nonlinear mapping, thereby perfectly solving nonlinear processing problems and ensuring that SVMs are able to produce relatively good results when trained on a small number of samples [31]. The SVM model has been proven more suitable for modeling small sample data in previous research [13,31].…”
Section: Methods Of Model Buildingmentioning
confidence: 99%
“…Kernel functions are introduced to realize nonlinear mapping, thereby perfectly solving nonlinear processing problems and ensuring that SVMs are able to produce relatively good results when trained on a small number of samples [31]. The SVM model has been proven more suitable for modeling small sample data in previous research [13,31]. In this paper, the optimum models for retrieving nutrient concentrations were determined by comparing model results from each ML method against empirical/in situ measurement data.…”
Section: Methods Of Model Buildingmentioning
confidence: 99%
See 1 more Smart Citation
“…This method uses internal implicit networks and structures to determine the complex characteristics of input data and obtain explicit relationships among the output variables [12,13]. Several approaches, including the decision tree [12,14], BP neural network [15,16], support vector machine model (SVM) [17,18], and extreme machine learning approaches [19], have strong adaptability, fault tolerance, and organization of data.…”
Section: Introductionmentioning
confidence: 99%